The energy consumption monitoring device via IoT and analytics on Ubidots - Mohd Roslan, Ahmad Afiq (2017)
Electricity is one of the useful energy in this world. Nowadays, the rating of uses of the electricity increase from year to year because most of the component needs the electricity to run [1]. The effective management of energy consumption of electricity can assist community to use the electricity in efficient path. Thus it can prevent the global warming. There are many ways to minimize the rating of the power consumption of electricity. In this project, an Internet of Things (IoT) system has been introduce to monitor the power consumption in the home. The Intel Edison devices was used to monitored about the power consumption usage in the home by sending alerts, suggestions, statics, graph which shall informed to their owner about the power consumption. This device connecting to the internet and transferring the data collected by them and store to the server [2]. By using Internet of Things (IoT) system, energy consumption of the home have been sent to the cloud to be analyze by using graph, pie chart and so on. With the huge number of things and sensors connected to the Internet, a massive and in some cases real-time data flow were automatically produced by connected things and sensors [3]. The data that have been collected were analyze everyplace as there is an internet connection [4].